A case of pulmonary visceral subpleural hematoma treated by hematoma evacuation during care of post-cardiopulmonary resuscitation - Yutaka Funaki; Kyoji Hirai (Journal of Cardiothoracic Surgery, 2024)
Abstract Background The occurrence of pulmonary visceral subpleural hematoma during care of post-cardiopulmonary resuscitation including chest compressions and anticoagulant and antiplatelet therapies is extremely rare. Also, there are few reports of treatment of visceral subpleural hematoma, most of which are treated by lung resection. Here we describe a rare case that pulmonary visceral subpleural hematoma arose during post-cardiopulmonary resuscitation care and was treated by hematoma evacuation. Case presentation A 58-year-old male with no smoking history and, past medical histories of rheumatoid arthritis, chronic atrial fibrillation, hypertension, diabetes, and dyslipidemia developed ventricular fibrillation due to myocardial infarction and fainted. He received bystander cardiopulmonary resuscitation and defibrillation by the ambulance crew and had return of spontaneous circulation. After transfer to our hospital, the patient underwent percutaneous catheter intervention and stenting with a diagnosis of myocardial infarction, followed by anticoagulant and antiplatelet therapies. On the 8th hospital day, chest radiography suggested right lower lobe pneumonia, and subsequent chest computed tomography revealed pulmonary hematoma in the visceral subpleural area from S6 to S10. Since no improvement was observed in hypoxemia, treatment was considered necessary. First, an attempt at computed tomography-guided drainage of hematoma was made, but insertion of the Pig-tail catheter was difficult due to hardness of the hematoma. Next, evacuation of hematoma was performed on the 13th hospital day. The hematoma was located in the visceral subpleural area and was removed by incising the pleura. TachoSil Tissue Sealing sheet and Polyglycoal acid sheet were applied to the sites of air leakage and oozing after hematoma evacuation. No re-bleeding or air leakage was observed after the treatment, and the patient was discharged on the 26th hospital day after an uneventful course. Conclusions Pulmonary visceral subpleural hematoma may occur during post-cardiopulmonary resuscitation care, including chest compressions and anticoagulant and antiplatelet therapies. In our case, CT-guided puncture and drainage was difficult and surgical treatment by incision of the visceral pleura and hematoma evacuation alone was done successfully.